Pengaruh Perceived Usefulness, Ease of Use, Security dan Risk terhadap Penggunaan E-wallet pada Mahasiswa Politeknik Negeri Padang - Aprilyani Wirheny Putri; Wiwik Andriani; Firman Surya (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2022)
This study was conducted to determine the effect of perceived usefulness, ease of use, security and risk on use behavior the e-wallet in Politeknik Negeri Padang students. This study uses a quantitative approach. The population of this study is Politeknik Negeri Padang students who use e-wallet. The sampling method in this study was non-probability sampling with accidental sampling technique so that a sample of 110 respondents was obtained. The data used is primary data obtained through the distribution of online questionnaires via google form. The hypothesis testing in this study used multiple linear regression analysis which was processed with the help of the IBM SPSS version 25 program. The results showed that the perceived usefulness and ease of use variables had a positive effect on use behavior the e-wallet, while the perceived security variable does not have a positive effect on use behavior the e-wallet, and the perceived risk variable does not negative effect on use behavior the e-wallet in Politeknik Negeri Padang students. In addition, simultaneously the variables of perceived usefulness, ease of use, security and risk effect on use behavior the e-wallet in Politeknik Negeri Padang students.